Prevalence and characteristics of multiple chemical sensitivity syndrome in women with reproductive dysfunction: A pilot survey single-center prospective study - E. V. Bolotova; L. V. Batrakova; A. V. Dudnikova; V. V. Onopriev; L. K. Kovaleva; I. G. Pavel’ev (Кубанский научный медицинский вестник, 2025)
Background. Multiple chemical sensitivity is an acquired and multifactorial syndrome characterized by a set of debilitating symptoms and triggered by low doses of environmental chemicals that are harmless to most people. The consequences of multiple chemical sensitivity have been studied to some extent; however, there are currently no studies specifically focused on multiple chemical sensitivity in the context of reproductive dysfunction. Objectives. To investigate the prevalence and characteristics of multiple chemical sensitivity syndrome in women with reproductive dysfunction. Methods. A pilot survey single-center prospective study was conducted at the consultative and diagnostic center of the clinic at Kuban State Medical University. The study involved 64 female patients with reproductive dysfunction and was carried out from September to December 2023. The primary endpoint of the study was to identify statistically significant associations between the presence of multiple chemical sensitivity and reproductive dysfunction in women. To assess the presence and severity of multiple chemical sensitivity symptoms, as well as their impact on daily life, a customized Russian-language version of the validated Quick Environmental Exposure and Sensitivity Inventory (QEESI) questionnaire was used. The questionnaire includes three subscales, each consisting of a block of 10 questions. Each question is scored from 0 to 10 points, with a maximum total score of 300 across all three subscales. The survey was conducted using the digital service EcoMedic (version 1.1 EcoKubMed), developed as part of the project. A diagnosis of multiple chemical sensitivity was established if the total score across all three subscales was 40 points or higher. Thus, two groups were formed: Group 1 — individuals diagnosed with multiple chemical sensitivity (n = 19), and Group 2 — individuals without multiple chemical sensitivity (n = 45). To assess reproductive dysfunction and metabolic disorders, laboratory tests were additionally performed. Statistical analysis of the study results was conducted using the Statistica 10.0 software package (StatSoft Inc., USA). When testing hypotheses, a significance level of p < 0.05 was considered statistically significant. Results. Among the types of chemical exposure, patients in Group 1 most frequently reported tobacco smoke, inhalation of car exhaust fumes, and the use of cleaning agents, with total scores of 189, 159, and 151 out of 190, respectively. When analyzing the second subscale, i.e., impact on daily life, in Group 1 patients, it was found that the most affected areas were the ability to work and study (175 out of 190), eating habits (154 out of 190), and the ability to do cleaning and other routine tasks (125 out of 190). The symptoms of multiple chemical sensitivity in Group 1 patients were most commonly related to the respiratory system (n = 11/19, 57.9%), the nervous system (n = 5/19, 26.3%), and the gastrointestinal tract (n = 3/19, 15.8%). The prevalence of abdominal obesity determined by the waist-to-hip ratio was higher in Group 1 patients compared to Group 2 patients (100% vs. 28.8%; χ2 = 7.514; p = 0.04, respectively). The correlation analysis revealed a moderate positive correlation between body mass index and QEESI questionnaire scores (r = +0.347, p = 0.02). Arterial hypertension and allergic diseases were reported significantly more often in Group 1 compared to Group 2 (χ2 = 6.354, p = 0.001 and 31.5% vs. 15.6%, χ2 = 5.17, p = 0.001, respectively). Statistically significantly higher levels of C-reactive protein (3.2 ± 0.1 mg/L vs. 1.9 ± 0.3 mg/L, p < 0.001), aspartate aminotransferase (24.7 ± 4.9 U/L vs. 14.5 ± 1.6 U/L, p < 0.001), homocysteine (7.8 ± 2.1 vs. 5.2 ± 1.2, p < 0.001), and a higher prevalence of dyslipidemia (31.5% vs. 13.3%, χ² = 5.514, p = 0.001) were observed in Group 1 compared to Group 2. Conclusion. According to test results, multiple chemical sensitivity syndrome was identified in 29.6% of female patients with reproductive disorders. A characteristic feature of the syndrome in this patient group was a higher prevalence of metabolic disorders.